A New Photoelectrocatalytic Water Purification System for Simultaneous Removal of Organic Pollutants and Heavy Metal Ions in Water - Peng Zhou; Yingming Xu; Tianhong Cui (Research)
A new photoelectrocatalytic water purification system was investigated by combining photocatalysis and electrochemistry. This configuration achieves simultaneous removal of both organic compounds and inorganic heavy metal ions from water by taking a carbon electrode as the working electrode and another electrode coated with a photocatalyst as the counter electrode. A negative bias potential is imparted onto the working electrode to induce the reduction of heavy metal ions, whereas the photocatalytic degradation of organic pollutants on the counter electrode is amplified via the transfer of photoexcited electrons from the counter electrode to the working electrode. Evaluations conducted in bulk solutions demonstrated that photoelectrocatalysis surpassed photocatalysis by yielding an organic matter degradation efficiency 2.3 times higher, successfully degrading 98% of a 10 μM methylene blue solution within 2 h. Simultaneously, the system realized the recovery of heavy metal ions, including copper, lead, and cadmium. This new photoelectrocatalytic water purification system was further integrated with microchannels, and the testing data affirm the substantial potential for system miniaturization.